Design of air-balloons for suppression of propeller cavitation induced hull-excitation at multi-frequencies. (1st June 2018) - Lee, Jeung-Hoon; Lee, Kyung-Jun; Kim, Boo-Ki
Abstract: The main objective of the present study is to establish a practical design strategy of air-balloons for a suppression of the propeller cavitation induced hull pressures at multi frequencies. Theoretical foundation is initiated with the existing modal series solution of a multiple scattering problem. An approximated form is then derived by a monopole regime which is valid in a low frequency range. Subsequent parametric analysis with a variation of the separation distance between the balloons provides an analytical evidence that the mutual interaction can be neglected unless they are too close to each other. Hence it is addressed that the individual balloon can be designed separately without a consideration of their coupling characteristics. Finally, the water tunnel test with two balloons demonstrates noticeable vibration reductions at the first- and second- order of blade passing frequencies by 72% and 59%, respectively. Highlights: Design method for multi-balloons is presented by use of the multiple scattering theory. Mutual interaction can be ignored unless the balloons are too close to each other. Cavitation test with two balloons showed a noticeable suppression of excitations at the first two orders of blade passing frequencies.